CHOROIDAL THICKNESS IN PATIENTS WITH CENTRAL SEROUS CHORIORETINOPATHY: Assessment of Haller and Sattler Layers. Issue 9 (September 2016) - Chung, Yoo-Ri; Kim, Jong Wan; Kim, Seung Woo; Lee, Kihwang
Abstract : Purpose: To investigate subfoveal choroidal thickness and subanalyze Haller and Sattler layers in eyes with central serous chorioretinopathy (CSC), uninvolved fellow eyes, and eyes of healthy controls using enhanced depth imaging optical coherence tomography. Methods: Ocular findings and clinical features of 31 eyes with CSC, 24 fellow eyes and eyes of 30 healthy controls were analyzed retrospectively from October, 2014 to March, 2015. Subfoveal choroidal thickness was measured using enhanced depth imaging optical coherence tomography, and the thicknesses of Haller and Sattler layers were analyzed. Results: Mean subfoveal choroidal thickness and mean thickness of Haller layer were significantly greater in CSC than in fellow eyes ( P = 0.043 and P = 0.036, respectively) and in normal control eyes ( P < 0.001 each), and those of fellow eyes in CSC patients were significantly thicker than those in normal control eyes ( P = 0.018 and P = 0.017, respectively). The thickness of Sattler layer did not differ significantly among these groups ( P = 0.519). Conclusion: Subfoveal choroidal thickness and the thickness of Haller layer were increased not only in affected but also in uninvolved fellow eyes of CSC patients. Nonvascular smooth muscle cells of the choroid may play a role in the pathophysiology of CSC, in response to increased sympathetic tone. Abstract : Subfoveal choroidal thickness and thickness of Haller layer were increased not only in eyes affected by CSC but also in uninvolved fellow eyes. Nonvascular smooth muscle cells of the choroid may play a role in CSC.